Reliability and validity of the Psychiatric Inpatient Patient Experience Questionnaire - Continuous Electronic Measurement (PIPEQ-CEM) - Hilde Hestad Iversen; Mona Haugum; Oyvind Bjertnaes (BMC, 2022)
Abstract Background The increasing emphasis on patient-centred care has accelerated the demand for high-quality assessment instruments, but the development and application of measures of the quality of care provided for mental health have lagged behind other areas of medicine. The main objective of this study was to determine the psychometric properties of the Psychiatric Inpatient Patient Experience Questionnaire - Continuous Electronic Measurement (PIPEQ-CEM), which consists of large-scale measurements from a Norwegian population. The change from cross-sectional surveys to continuous measurements necessitated further validation of the instrument. The secondary objective was to develop a short version of the PIPEQ-CEM. Methods The data included responses from the first year of continuous measurement, and included adult inpatients (age ≥ 18 years) who received specialized mental healthcare from 191 different sections in Norway (n = 3,249). Missing data, ceiling effects, factor structure and internal consistency levels were assessed. The short scale was developed by exploring missing items, ceiling effects, results from exploratory factor analysis (EFA) and item performance from item response theory (IRT) analyses. Results Psychometric testing supported previous results and illustrated that the PIPEQ-CEM comprises three empirically based scales with good internal consistency, reliability and validity, and covers structure and facilities, patient-centred interactions, and outcomes. A seven-item short form was developed, which provides an efficient approach for brief yet comprehensive measurements that can be applied in the future. Conclusion The PIPEQ-CEM can be recommended for use in future national surveys that assess patient experience with inpatient psychiatric care in Norway and in other countries with similar healthcare systems. The short form can be applied where respondent burden and cognitive load are crucial issues.